THE ROLE OF THE WORK-FAMILY CONFLICT IN THE RELATIONSHIP BETWEEN WORK-FAMILY CULTURE AND EMPLOYEE WELL-BEING - Putri, Hilda Elsa; Etikariena, Arum (Faculty of Psychology, Diponegoro University, 2020)
This study aims to determine whether the work-family conflict plays a role as a mediator in the relationship between work-family culture and employee well-being. Data were gathered from three automotive company branches in Lampung, Indonesia using purposive sampling, with N = 165 (80% male; average age 25 years, SD = 7.90). The analysis method for this study was a simple mediation test with Hayes’ (2013) PROCESS macro. The result of the study showed that there were no significant positive effects of work-family culture on employee well-being, t(162) = .29, p = .76. On the other hand, work-family culture had significant effects on work-family conflict (a = .58) and work-family conflict had significant effects on employee well-being (b = .61). In line with the research hypothesis, there was an indirect relationship between work-family culture and employee well-being through work-family conflict as a mediator (ab = .35). We used the perceived organizational support (POS) theory as a framework and spillover theory to interpret the results. The findings of this study provide insights that it pays off to invest in a work-family culture because such culture is expected to give optimum advantages on well-being at work.